Asesmen Kompetensi Minimum (AKM) berbasis literasi numerasi pada pembelajaran MI/SD - Alviani, Fauziah Ninik (Maliki Interdisciplinary Journal, 2023)
National Assessment (AN) as a new breakthrough to replace the National Examination (UN). Because young people in Indonesia have low literacy skills and a lack of interest in reading, the government has implemented this minimum competency assessment. Where the Minimum Competency Assessment only measures minimal knowledge in two areas of cognition namely literacy and numeracy. Literacy understanding is divided into the first three namely writing ability, knowledge and skills as well as the ability to manage information and knowledge for application in everyday life. Numeration includes the ability to apply mathematical ideas and principles to problems that are often unstructured, have many possible solutions, or may not have any solutions at all. In this AKM or Minimum Competency Assessment, there are three important components, all three of which represent the notion of literacy and numeracy. The AKM components are content, context, and cognitive level.